Experience, research, and facts related to local species of paddy - Mali, Chapel Div Bhagat; Chaudhary, Pashupati; Chaudhary, Parmananda (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
This paper presents a discussion of the qualities of local species of paddy rice, along with the advantages of growing it-marketability, flavor, and use in religious ceremonies-from a farmer's perspective. It also compares production technologies tor local paddy and improved varieties, with information on traditional techniques for seed management.